Rejected Products from Creamer and Milk Industry as Feeding Substrate for Maggot – Green Technology for Industrial Organic Waste Management and Circular Bioeconomy - Rodlia Fitriana Aulia; Yekti Bagastyo Arseto; Rizkivia Radita Deqi (BIO Web of Conferences)
The creamer and milk industries produce organic waste, including rejected products. The rejected products have potential as maggot-feeding substrates. This research consists of two preliminary studies. This study analyzed the effects of substrate composition and the addition of milk-rejected on larval growth. The substrates were creamer (A), fruit-vegetable waste (B), and rejected bread (C). The dry weights of A:B:C in the first preliminary study: 5:2.5:2.5; 5:2:3; 5:1:4; 6:2:2; 6:1:3; 4:3:3; 4:2:4; and 4:1:5. The feeding rate was 40mg/larva.day per 2 days. The optimal compositions were 5:2.5:2.5 and 4:3:3. The larval mass reached 0.236 and 0.187 g/larva, and the Growth Rates were 6.45 and 4.39 g/day. The WRI was 5.46% and 4.19%. More creamer inhibited maggot growth due to the sticky substrate, which inhibited their respiration and movement. Maggot also requires a balanced B:C composition. These compositions were tested in the main research and added 1 more variation (3:3.5:3.5). Rejected milk has a positive effect on maggot growth. At the same composition, the highest average masses were 0.192 g/l (milk addition) and 0.187 g/l (without milk addition). It was concluded that rejected creamer and milk can be used as substrates for maggots with a balanced composition of other waste.